The Application of Solution-Focused Therapy Intervention Module to help Individuals Experiencing Psychological Distress in Organization - Rose, Nurul Naimah; Abdullah, Shuhairimi; Ishak, Aida Shakila (Asian Social Work Journal, 2024)
This study is a descriptive study of developing a solution-focused therapy as a counselling intervention module for individuals experiencing psychological distress. This module was built based on the Sidek’s module development model that includes the principles of module construction. This counselling intervention model is specifically designed to help individuals with psychological distress to reduce their symptoms. Solution-focused therapy was chosen as an aid because the techniques in this therapy focus more on solution rather than the problem, counselling sessions are simple and brief with minimal cost. There are nine (9) experts consisting of counselling practitioners and counselling academics experts participating as module expert evaluator. The Pearlin's theory of distress psychology is used in this study as a theoretical foundation to understand the distress psychology and its symptoms. Overall, the experts found that the content of the module is suitable for the target audiences with an acceptable evaluation score. Solution focused therapy embedded in a module is a good initiative and can be strengthened further to be used by counselling practitioners in a real setting.